From green buildings to living buildings? Rating schemes and waste management practices in Australian educational buildings. Issue 4 (19th August 2020) - Udawatta, Nilupa; Zuo, Jian; Chiveralls, Keri; Zillante, George
Abstract : Purpose: There is an increasing level of recognition of the pressing issues associated with climate change and resource depletion. As a result, it is well recognised that higher education institutions bear responsibilities to promote "sustainable development". Many universities have adopted green building practices in the construction of their building infrastructure. A variety of Green Building Rating Tools (GBRTs) have been designed to facilitate green building developments. Thus, the aim of this research is to identify mechanisms to improve current GBRTs in terms of waste management (WM) practices by using green star accredited educational buildings in Australia. Design/methodology/approach: A qualitative approach was adopted in this study to achieve the research aim by conducting three case studies of educational buildings in South Australia. Thirty three interviews were carried out in a face-to-face, semi-structured manner and project documentations were reviewed. The participants were asked to provide their expert opinions on the GS initiative and its ability to minimise waste generation, the impact of the GS initiative on solid WM practices and problems associated with the implementation process of the GS initiative. Data was analysed using code-based content analysis using the NVivo software package. Tables and figures were used as the visualization technique to present an expedient understanding in a holistic manner. Findings: Findings showed that the Green Star (GS) initiative drives change in the way current practices are performed in the Australian construction industry. However, this study revealed that WM targets outlined in the GS initiative are not challenging enough. Thus, suggestions are provided in this research to improve the WM aspects of GS initiatives by looking beyond a focus on "sustainability" and "waste minimisation" towards a focus on regenerative environments. Originality/value: These findings are valuable for practitioners and policymakers seeking to improve WM practices and to address issues associated with climate change and resource depletion.